Pattern-assisted stacking colloidal quantum dots for photonic integrated circuits. Issue 29 (15th July 2019) - Rong, Kexiu; Liu, Hui; Shi, Kebin; Chen, Jianjun
Abstract : The simple pattern-assisted stacking approach using the same material is proposed to construct on-chip photonic components for integrated circuits. Abstract : In photonic integrated circuits (PICs), on-chip light sources and other photonic devices are usually made of different materials. The complexity and compatibility brought about by different materials and various structures in a single chip considerably increase the fabrication and integration difficulties. Here, we propose to stack the same nanoscale building blocks [colloidal quantum dots (CQDs) with both large gains and high refractive indices] in predefined trench patterns to address the fabrication and integration problems of PICs. By employing this simple approach of using the same material (CdSe/ZnS CQDs), the on-chip integration of more than 10 CQD-based photonic components (including the laser, low-noise amplifier, bending waveguide, Y-splitter, Mach–Zehnder interferometer, and grating) is experimentally demonstrated. In particular, the integrated low-noise amplifier (net gain coefficient >600 cm −1 ) addresses the absorption loss problem brought about by the utilization of the same material. Moreover, the little influence of the CQD layer on the CQD nanophotonic components facilitates the fabrication and is beneficial for large-scale integration. This simple fabrication approach with a flexible integration strategy may provide a possible platform to construct functional PICs.